2019
DOI: 10.1002/cam4.2183
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and therapeutic options in non‐small cell lung cancer patients with concomitant mutations of EGFR, ALK, ROS1, KRAS or BRAF

Abstract: Background Although oncogenic driver mutations were thought to be mutually exclusive in non‐small cell lung cancer (NSCLC), certain tumors harbor co‐occurring mutations and represent a rare molecular subtype. The evaluation of the clinical features and therapeutic response associated with this NSCLC subtype will be vital for understanding the heterogeneity of treatment response and improving the management of these patients. Methods This retrospective study included 3774 samples from patients diagnosed with NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 42 publications
4
42
0
Order By: Relevance
“…Our findings were consistent with our previous study using the same panel of genes and reporting a similar mutation rate of 63.6% in a smaller cohort of 59 Vietnamese NSCLC patients 32 . The mutation profiles of Vietnamese NSCLC patients also exhibited certain common features of NSCLC patients previously reported 33,34 . Firstly, mutations in EGFR and KRAS are the most common, accounted for more than 50% of total cases, while mutations in ALK, BRAF, NRAS and ROS1 were rarer.…”
Section: Discussionsupporting
confidence: 57%
“…Our findings were consistent with our previous study using the same panel of genes and reporting a similar mutation rate of 63.6% in a smaller cohort of 59 Vietnamese NSCLC patients 32 . The mutation profiles of Vietnamese NSCLC patients also exhibited certain common features of NSCLC patients previously reported 33,34 . Firstly, mutations in EGFR and KRAS are the most common, accounted for more than 50% of total cases, while mutations in ALK, BRAF, NRAS and ROS1 were rarer.…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, several studies have reported that different orders of treatment lines of EGFR‐TKI and ALK‐TKI affect the therapeutic outcomes of this subgroup of patients . Moreover, numerous studies reported that EGFR mutation and ALK rearrangements may coexist in the same tumor cells or may occur in different lesions of the tumor, which may have an effect on the treatment strategies . As ctDNA was released from tumor lesions of the whole body, the result of ALK/EGFR co‐alteration from ctDNA should be further verified by tissue samples from different tumor foci in patients with multifocal NSCLC if possible, in order to clarify the intratumoral or intertumoral coexistence of such co‐alteration and guide the subsequent therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that targetable activating alterations in lung cancer genes, such as EGFR, ALK, RET and ROS1, are mutually exclusive molecular events. 30 Recently, however, some cases of NSCLC with coalteration have been reported in the literature, [38][39][40][41] and these coaltered patients may benefit from treatment with more than one targeted drug. 42 There were 33 cases (3.7%) with coalteration in our study, including EGFR/PIK3CA (2.1%, 19 cases), EGFR/HER2 (0.7%, six cases), HER2/KRAS (0.3%, three cases), EGFR/KRAS (0.1%, one case), EGFR/ ROS1 (0.1%, one case), EGFR/NRAS (0.1%, one case), KRAS/PIK3CA (0.1%, one case), and a triple KRAS/ PIK3CA/HER2 (0.1%, one case) coalteration.…”
Section: Discussionmentioning
confidence: 99%
“…43 PIK3CA mutations frequently coexist with EGFR or KRAS mutations. Evidence has suggested that the combination of KRAS and EGFR mutation may have a negative impact on the efficacy of TKI treatment, 41 but EGFR-TKI may be an effective choice for the treatment of patients with NSCLC with comutation of EGFR/KRAS. 44 Zeng et al 45 reported a case of adenocarcinoma having acquired GOPC-ROS1 rearrangement after treatment with osimertinib.…”
Section: Discussionmentioning
confidence: 99%